A novel in situ urinary bladder model for studying afferent and efferent mechanisms in the micturition reflex in the rat. Issue 5 (29th May 2013) - Aronsson, Patrik; Carlsson, Thomas; Winder, Michael; Tobin, Gunnar
Abstract Aims The search for new animal models to investigate both efferent and afferent levels of the micturition reflex, to better understand urinary dysfunctions, is of great importance. Therefore in this study we developed and characterized, by comparisons with a conventional whole bladder model, a novel in situ model. Methods The urinary bladder was carefully prepared and separated, via a midline incision, into two halves all the way to the urethra in pentobarbitone and medetomidine anesthetized male rats. The separated bladder halves (with no direct connection) were immobilized with ligatures to the underlying tissue. The tension could thereafter be recorded at one side, while the other half was occasionally stretched in order to evoke an afferent signal. Also, injections of ATP and methacholine and electric nerve stimulation were employed. Results Ipsilateral stretch of 30 and 50 mN induced a force‐dependent contractile response on the contralateral side. Moreover, electrical stimulation of efferent pelvic nerve fibers, and intravenous injections of methacholine and ATP, evoked dose‐dependent contractions, resembling responses observed in the whole bladder model. Here, the threshold frequency at electrical stimulation of the efferent fibers was <2 Hz and the maximum response appeared at 10–20 Hz, while afferent stimulation had a threshold of 5–10 Hz with the maximum response at 40 Hz. Conclusions In the current study we show that stimulation of afferents at one side of the bladder induces, via impulses from the central nervous system, contractions from the other side. This novel model enables quantitative comparisons of changes occurring within the micturition reflex arc in bladder disorders. Neurourol. Urodynam. 33:550–557, 2014. © 2013 Wiley Periodicals, Inc.